Electricity Market-oriented Reform Empowers the "Dual Carbon" Strategy: Carbon Emission Reduction Paths and Heterogeneity Tests of Spot Market Pilot Policies - Chen, Tangjie; Y, LongFei; Yan, JiaCheng; Ding, SongJun; TU, QIANGNAN (Economics & Management Review, 2025)
Under the dual pressure of increasing energy demand and reducing carbon emissions to protect the environment, the carbon reduction effect and dynamic transmission mechanism of the pilot policy of electricity spot market need to be systematically evaluated. Based on the panel data of 30 provincial-level regions in China from 2017 to 2021, this paper empirically tests the impact of policy on carbon emission intensity and its regional heterogeneity by using the panel fixed effect model, mediating effect analysis and moderating effect analysis. The findings are as follows: (1) In the short term, the imperfect market mechanism increases the dependence on thermal power, leading to a significant rise in carbon emissions. However, in the long run, the synergistic effect of industrial structure upgrading, low-carbon technology innovation and increased environmental awareness effectively reduces the emission intensity. (2) Prominent regional heterogeneity: high financial development regions inhibit emissions through technology diffusion and service industry transformation, while low financial development regions face carbon lock-in due to thermal power dependence. High sustainability regions accelerate emission reduction through innovation network externalities, while low sustainability regions require technological catch-up strategies to overcome path dependence.